Effect of statin therapy on vaspin levels in type 2 diabetic patients - Al-Azzam SI; Alzoubi KH; Abu Abeeleh J; Mhaidat NM; Abu-Abeeleh M (Dove Medical Press, 2013)
Sayer I Al-Azzam,1 Karem H Alzoubi,1 Jaafar Abu Abeeleh,2 Nizar M Mhaidat,1 Mahmoud Abu-Abeeleh31Department of Clinical Pharmacy, Faculty of Pharmacy, Jordan University of Science and Technology, Irbid, 2Department of Pharmacy, Royal Medical Services, Amman, 3Department of Surgery, Division of Cardiothoracic Surgery, Faculty of Medicine, The University of Jordan, Amman, JordanBackground: Statins are commonly used antihyperlipidemic agents, with anti-inflammatory and immunomodulatory properties that are thought to account for a significant portion of their ability to protect against atherosclerosis and cardiovascular disease. Vaspin, a visceral adipose tissue-derived serine protease inhibitor, is an emerging adipokine with important insulin-sensitizing, cardioprotective, and antiatherosclerotic properties in patients with diabetes. In this randomized controlled clinical trial, we evaluated the effect of statin therapy on vaspin levels in patients with type 2 diabetes mellitus.Methods: Patients were divided into two groups, ie, those receiving simvastatin (study group, n = 33), and those who did not (control group, n = 29). Patient data, blood biochemistry, and vaspin levels were recorded at the beginning of the study (baseline) and after 8 weeks (end of the study).Results: After 8 weeks of treatment, vaspin levels were increased in patients treated with simvastatin (504.58 ± 203.07 pg/mL at baseline versus 629.15 ± 68.39 pg/mL after 8 weeks, P < 0.01), but not in patients who were not treated with simvastatin (613.33 ± 357.53 pg/mL at baseline versus 582.37 ± 84.63 pg/mL after 8 weeks, P > 0.05). In addition, the lipid-lowering effect of simvastatin was reflected in a statistically significant reduction in total cholesterol in the study group (220.75 ± 55.66 mg/dL at baseline versus 201.90 ± 53.65 mg/dL after 8 weeks P < 0.01) but not in the control group (214.24 ± 47.2 mg/dL at baseline versus 215.72 ± 43.65 mg/dL after 8 weeks, P > 0.05) and in a statistically significant reduction in triglyceride levels in the study group (265.8 ± 210.41 mg/dL at baseline versus 223.03 ± 178.67 mg/dL after 8 weeks, P < 0.05) but not in the control group (225.44 ± 115.13 mg/dL at baseline versus 215.58 ± 110.2 mg/dL after 8 weeks, P > 0.05). Mean vaspin levels were significantly higher in the study group than in the control group.Conclusion: These results indicate that statin therapy increases plasma vaspin levels in addition to having a lipid-lowering effect. This could be a mechanism underlying the pleiotropic effects seen with statins, including their cardioprotective and antiatherosclerotic effects.Keywords: vaspin, statins, diabetes, adipokines